Inspection and maintenance of stormwater control measures (American Society of Civil Engineers, 2019)
Inspection and Maintenance of Stormwater Control Measures describes the functions and operations of stormwater control measures, offers trouble-shooting suggestions, and provides valuable information on the implementation of inspection and maintenance procedures. Topics include Maintenance Guidelines and Protocols Tiered Inspection and Maintenance Vegetated Conveyance Practices Filtration and Infiltration Practices Surface Storage Practices Literature Review Findings, and National BMP Survey results and recommendations. The field of stormwater management has experienced exponential innovation over the last decade. Unlike the treatment technologies implemented to address point source pollution, non-point source pollution controls have no universally agreed upon maintenance protocols. Despite lack of universal maintenance protocols many states and municipalities have made regular inspection and maintenance of stormwater best management practices (BMPs) an ongoing legal requirement. The various maintenance tasks required for BMPs may serve to not only meet legal requirements, but also to ensure proper BMP function and to prevent flooding and negative impacts to adjacent infrastructure. Engineers, landscape architects, land planners, stormwater professionals, asset managers, maintenance personnel, and government officials will find this guidance document a valuable resource in inspection and maintenance planning, as well as in the field.